2012
DOI: 10.1371/journal.pone.0047077
|View full text |Cite
|
Sign up to set email alerts
|

Increased T Regulatory Cells Are Associated with Adverse Clinical Features and Predict Progression in Multiple Myeloma

Abstract: BackgroundRegulatory T (Treg) cells play an important role in the maintenance of immune system homeostasis. Multiple myeloma (MM) is a plasma cell disorder frequently associated with impaired immune cell numbers and functions.MethodsWe analyzed Treg cells in peripheral blood (n = 207) and bone marrow (n = 202) of pre-malignant and malignant MM patients using flow cytometry. Treg cells and their subsets from MM patients and healthy volunteers were functionally evaluated for their suppressive property. A cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
120
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(126 citation statements)
references
References 48 publications
6
120
0
Order By: Relevance
“…These observations are in accordance with observations made in several other malignancies [56], and suggest that MM cells evade immune surveillance partially through the increase of suppressive Tregs [60]. The myeloma-promoting role of Tregs is reinforced by observations in MM patients showing a shorter survival for patients with high Treg percentages [50] and indicating that the number of Tregs is a predictive marker for the risk of disease progression [60]. The finding that MM cells are able to induce the generation of Tregs in vitro further corroborates these results [61].…”
Section: Regulatory/suppressive Cellssupporting
confidence: 92%
See 2 more Smart Citations
“…These observations are in accordance with observations made in several other malignancies [56], and suggest that MM cells evade immune surveillance partially through the increase of suppressive Tregs [60]. The myeloma-promoting role of Tregs is reinforced by observations in MM patients showing a shorter survival for patients with high Treg percentages [50] and indicating that the number of Tregs is a predictive marker for the risk of disease progression [60]. The finding that MM cells are able to induce the generation of Tregs in vitro further corroborates these results [61].…”
Section: Regulatory/suppressive Cellssupporting
confidence: 92%
“…Initially, a decrease in Treg numbers was reported in MM patients, along with a defect in their ability to suppress T-cell proliferation [57]. In contrast, several more recent studies have concluded that the number of functionally intact Treg is increased in MM patients [49,50,[58][59][60]. These observations are in accordance with observations made in several other malignancies [56], and suggest that MM cells evade immune surveillance partially through the increase of suppressive Tregs [60].…”
Section: Regulatory/suppressive Cellsmentioning
confidence: 65%
See 1 more Smart Citation
“…Tregs have been attributed to suppress immunoglobulin production and secretion without affecting proliferation of the myeloma cells 20, a phenomenon which has been found to be isotype specific 21, 22. Tregs suppress antitumor cytotoxicity 23, and increased Tregs levels have been linked with shorter survival in various cancers 24 and in multiple myeloma 19, 25. More specifically, increased Treg levels in myeloma were found to correlate with low polyclonal plasma cell numbers, adverse clinical features and shorter survival 25.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs suppress antitumor cytotoxicity 23, and increased Tregs levels have been linked with shorter survival in various cancers 24 and in multiple myeloma 19, 25. More specifically, increased Treg levels in myeloma were found to correlate with low polyclonal plasma cell numbers, adverse clinical features and shorter survival 25. Accordingly, in multiple myeloma patients with long standing disease control and survival, significantly lower numbers of Tregs were found compared to patients with active disease 26, 27.…”
Section: Discussionmentioning
confidence: 99%